FlipHTML5 Assisted E-Book to Improving Elementary School Students' Motivation - Handiar, Afifah; Zulherman (International Journal of Elementary Education, 2023)
The utilization of learning media has the potential to captivate and motivate students, as it can enhance the clarity of message and information delivery, thereby facilitating and optimizing the learning experience and outcomes. This research aims to create a FlipHTML5 assisted E-book that can be a proficient educational tool to enhance motivation and academic achievements. The present study employs research and development (R&D) methodology utilizing the ADDIE development model, comprising five stages, Analysis, Design, Development, Implementation, and Evaluation. The product undergoes validation by experts in the relevant fields of material, media, and language, followed by an assessment of media efficacy through a pretest-posttest methodology. The validation outcomes indicate that material experts weighed an average score of 78%, placing it in worthy category. Media experts, on the other hand, weighed an average score of 89%, positioning it in very worthy category. Lastly, language experts weighed an average score of 76%, placing it in worthy category. The present study examines the efficacy of utilizing the FlipHTML5 platform to facilitate the human respiratory system learning material. The study employed N-Gain analysis and a T-Test to discern disparities between the experimental and control groups. The findings indicated that the E-book's development enhanced students' motivation and learning outcomes. Consequently, this research has contributed valuably to establishing a conducive learning environment well-suited for educational purposes.